The Influence of Work Discipline and Compensation on The Employees Performance of National Civil Capital Malangbong Garut Branch - Nuryani, Mita; Sarah, Siti (Dinasti International Journal of Digital Business Management, 2024)
The era of globalization where all companies are developing increasingly rapidly requires companies to optimize the performance of their employees and requires human resources. Therefore, good performance will not only benefit individuals, but institutions or organizations and society will also benefit. The purpose of this research is to determine thedescription and influence of Work Discipline, Compensation on Employee Performance at Madani National Capital(PNM) Malangbong Garut Branch. This research was conducted on 35 employees of Permodalan Nasional Madani (PNM) Malangbong Garut Branch using the method of distributing questionnaires, path analysis and hypothesis testing. Based on the research results, it shows that the description of Work Discipline is in the quite good category at 3.21,Compensation is in the quite good category at 3.38 and Employee Performance is in the quite good category at 2.71. The influence of Work Discipline on Employee Performance is 32.8%. The influence of compensation on employee performance is 20% and the influence of work discipline and compensation on employee performance is 84.2%. The conclusion of this research is that there is a significant influence between Work Discipline and Compensation on Employee Performance at Permodalan Nasional Madani (PNM) Malangbong Garut Branch.